STRATEGI PENGELOLAAN DESTINASI WISATA PEMANDIAN AIR PANAS UNTUK MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN DI GUNUNG PANJANG TUMARITIS, BOGOR - Tevila Akwila; Rizki Nurul Nugraha (LPSDI Bina Patria, 2024)
This study aims to analyze the management strategy of Gunung Panjang Tumaritis hot spring tourist destination in Bogor in an effort to increase the number of tourist visits. A tourist destination is an area that has the potential to be developed as a destination for tourism visits. Tourist destinations can be natural, cultural and artificial. In this research, Gunung Panjang Tumaritis hot spring is one of the artificial tourist destinations in Bogor Regency. Gunung Panjang Tumaritis hot spring is one of the tourist destinations that has great potential to be developed, but still faces several challenges related to its management. This research uses qualitative decriptive data analysis techniques and uses quailtative data analysis tools in the form of Nvivo 12 software. Despite having implemented management strategies, the results of this study show that the management of this destination still needs effective improvement and has not shown a significant increase in visits.This research is expected to provide input for destination managers in an effort to develop and manage Gunung Panjang Tumaritis hot springs more optimally, so as to attract more tourist visits.